Default Values in Allen Ginzberg’s A Supermarket in California - Vinogradovas, Michailas (Respectus Philologicus, 2003)
In the present paper some tenets of schema theory are used for the inferencing of information from literary texts. The concrete task of the study is to show how differences in default expectations may contribute to the interpretation of a literary text. For this purpose, the analysis of Allen Ginzberg’s A Supermarket in California is carried out. From a schema-theory perspective, worlds generated by verbal texts are cognitive structures, and a text world corresponds to schemata instantiated by the reader during the processing of the text that depends on the reader’s background assumptions. Background assumptions, shared by the members of the same language community, are regarded as default values, and they include default properties of a schema, default participants, etc. A metaphor expressing some similarity between human life and shopping is a surface metaphor since it is too general and abstract. The surface metaphor may be concretized through the explication of the discrepancies between the default properties normally characteristic of a real SUPERMARKET schema and the properties attributed to this schema in the text. Such concretization turns this surface metaphor into the deep one which signifies the prevalence of material values in the contemporary ethos and mores.